Zircon M127 – A Homogeneous Reference Material for SIMS U–Pb Geochronology Combined with Hafnium, Oxygen and, Potentially, Lithium Isotope Analysis. Issue 4 (16th July 2016) - Nasdala, Lutz; Corfu, Fernando; Valley, John W.; Spicuzza, Michael J.; Wu, Fu‐Yuan; Li, Qiu‐Li; Yang, Yue‐Heng; Fisher, Chris; Münker, Carsten; Kennedy, Allen K.; Reiners, Peter W.; Kronz, Andreas; et al.
Abstract : In this article, we document a detailed analytical characterisation of zircon M127, a homogeneous 12.7 carat gemstone from Ratnapura, Sri Lanka. Zircon M127 has TIMS‐determined mean U–Pb radiogenic isotopic ratios of 0.084743 ± 0.000027 for 206 Pb/ 238 U and 0.67676 ± 0.00023 for 207 Pb/ 235 U (weighted means, 2 s uncertainties). Its 206 Pb/ 238 U age of 524.36 ± 0.16 Ma (95% confidence uncertainty) is concordant within the uncertainties of decay constants. The δ 18 O value (determined by laser fluorination) is 8.26 ± 0.06‰ VSMOW (2 s ), and the mean 176 Hf/ 177 Hf ratio (determined by solution ICP‐MS) is 0.282396 ± 0.000004 (2 s ). The SIMS‐determined δ 7 Li value is −0.6 ± 0.9‰ (2 s ), with a mean mass fraction of 1.0 ± 0.1 μg g −1 Li (2 s ). Zircon M127 contains ~ 923 μg g −1 U. The moderate degree of radiation damage corresponds well with the time‐integrated self‐irradiation dose of 1.82 × 10 18 alpha events per gram. This observation, and the (U–Th)/He age of 426 ± 7 Ma (2 s ), which is typical of unheated Sri Lankan zircon, enable us to exclude any thermal treatment. Zircon M127 is proposed as a reference material for the determination of zircon U–Pb ages by means of SIMS in combination with hafnium and stable isotope (oxygen and potentially also lithium) determination. Key Points: Zircon M127, a 12.7 carat gemstone from Ratnapura (Sri Lanka) is proposed as a SIMS reference material. The material has a concordant 206 Pb/ 238 U age of 524.36 ± 0.16 Ma (95% confidence). M127 will be used and distributed by the Beijing SHRIMP Centre, Chinese Academy of Geological Sciences (liudunyi@bjshrimp.cn ).